Fiscal implications of central bank balance sheet policies - Athanasios Orphanides (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2016)
Under ordinary circumstances, the fiscal implications of central bank policies tend to be seen as relatively minor and escape close scrutiny. The global financial crisis of 2008, however, demanded an extraordinary response by central banks which brought to light the immense power of central bank balance sheet policies as well as their major fiscal implications. Once the zero lower bound on interest rates is reached, expanding a central bank's balance sheet becomes the central instrument for providing additional monetary policy accommodation. However, with interest rates near zero, the line separating fiscal and monetary policy is blurred. Furthermore, discretionary decisions associated with asset purchases and liquidity provision, as well as with lender-of-last-resort operations benefiting private entities, can have major distributional effects that are ordinarily associated with fiscal policy. In the euro area, discretionary central bank decisions can have immense distributional effects across member states. However, decisions of this nature are incompatible with the role of unelected officials in democratic societies. Drawing on the response to the crisis by the Federal Reserve and the ECB, this paper explores the tensions arising from central bank balance sheet policies and addresses pertinent questions about the governance and accountability of independent central banks in a democratic society.
urn:nbn:de:hebis:30:3-410439
Keywords: E52; E58; E61; G01; H12; 330; quantitative easing; lender of last resort; monetary financing; loss sharing; central bank independence; central bank accountability; central bank governance; rules vs discretion